Absorption and scattering by fractal aggregates and by their equivalent coated spheres. (January 2015) - Kandilian, Razmig; Heng, Ri-Liang; Pilon, Laurent
Abstract: This paper demonstrates that the absorption and scattering cross-sections and the asymmetry factor of randomly oriented fractal aggregates of spherical monomers can be rapidly estimated as those of coated spheres with equivalent volume and average projected area. This was established for fractal aggregates with fractal dimension ranging from 2.0 to 3.0 and composed of up to 1000 monodisperse or polydisperse monomers with a wide range of size parameter and relative complex index of refraction. This equivalent coated sphere approximation was able to capture the effects of both multiple scattering and shading among constituent monomers on the integral radiation characteristics of the aggregates. It was shown to be superior to the Rayleigh–Debye–Gans approximation and to the equivalent coated sphere approximation proposed by Latimer. However, the scattering matrix element ratios of equivalent coated spheres featured large angular oscillations caused by internal reflection in the coating which were not observed in those of the corresponding fractal aggregates. Finally, the scattering phase function and the scattering matrix elements of aggregates with large monomer size parameter were found to have unique features that could be used in remote sensing applications. Abstract : Highlights: Fractal aggregate radiation characteristics were computed by the T-matrix method. Fractal aggregates of spherical monomers can be approximated as coated spheres. Coated spheres should have the same volume and average projected area as aggregates. Equivalent coated spheres captured shading and multiple scattering effects. Approximation is valid for a wide range of monomer size and aggregate morphologies.